The influence of biological regeneration on the recovery of volleyball players during the competition season - Ziółkowski, Bartosz; Schroeder, Liwiusz; Biesiada, Krzysztof; Miler, Adrian (Journal of Education, Health and Sport, 2025)
One of the many online and regeneration services that are available is biological regeneration, which is nowadays the common regeneration of our body. Thanks to its influence on the human body, it was used in the port. The sports body undergoes various injuries during long hours of training, resulting in micro-injuries. Accessibility to athlete and athlete performance. To level and apply regenerative processes, apply regenerative applications including. Impact on every improvement, including mental health. The aim of work was to find an answer to the question "Does biological renewal have a positive effect on the stimulation of regenerative processes in people practicing professional sports." Material and method: The survey was conducted via an anonymous online survey. Consisting of 23 questions. The research covered clubs representing various competition classes, such as: Sports Clubs: # VolleyWrocław, E.LECLERC MOYA Radomka Radom, Joker Świecie, Polskie Przetwory Bydgoszcz, LUKS Wilki Wilczyn, Sokół Mogilno, LZS Orzeł SuperGadget Osiecza, Sports Club Częstochowianka Results :After collecting complete information, 94% of the respondents confirmed the positive effect of biological regeneration, influencing the improvement of regenerative processes and readiness for further training units. The main factor of changes was faster regeneration between units, as well as the players' satisfaction with biological regeneration treatments. The majority of 82% of the respondents confirmed the positive effects of the treatments, and also felt significant differences after performing them. Conclusions: Selected biological regeneration treatments, such as: sports, sauna, local cryotherapy, and relaxing massage significantly improve the regeneration of the player's body, thus contributing to reducing the possibility of an injury, as well as greater readiness for the next training unit. The research results confirm the beneficial effect of biological regeneration on the athlete's body. The above work confirms the claim that biological regeneration is an inherent factor in sport.